Global modern monitoring systems for PV based power generation: A review. (February 2018) - Rahman, M.Mahbubur; Selvaraj, J.; Rahim, N.A.; Hasanuzzaman, M.
Abstract: Photovoltaic system is widely installed to increase the share of renewable energy as well as to reduce the environmental impact of fossil fuel based energy. Photovoltaic (PV) is one of the most potential renewable energy based power generation systems. Monitoring of PV system is very important to send information that allows owners to maintain, operate and control these systems to reduce maintenance costs and to avoid unwanted electric power disruptions. Different monitoring systems have been introduced with the time following different requirements. Circuit complexity, availability of friendly graphical user interface, easy to understand system architecture, maintenance facility and customization ability for end user differ from system to system along with cost issues. This paper provides an overview of architectures and features of various PV monitoring systems based on different methods. There are various technologies for PV monitoring and control, developed as for commercial use or research tasks. It has been seen that a large portion of the work is done on classifications, for example, Internet based Monitoring using Servers, TCP/IP, GPRS and so forth. There are various methodologies for data acquisition, for example, PLC (Power Line Communication), PIC, Reference cell, National Instruments etc. Various requirements are considered while selecting a proper monitoring system for an application. Review of various monitoring technologies with system attributes and working structures have been discussed to get a clear view of merits and demerits of existing PV monitoring systems. All the systems discussed in this paper have pros and cons, and these systems were developed following different requirements. In the end, a particular cost effective monitoring system using Arduino microcontroller has been proposed considering both research and user level requirements from perspectives of cost, availability of parts/modules and features, compatibility with sensors and end-devices etc.